Research on power increase adaptive control strategy based on 5 MW wind turbine. (April 2021) - Ying, Deng; Rashid, Asif; Sheng, Liu He; De, Tian; Shize, Tang; Iqbal, Atif
Abstract: Wind power is one of the cheapest and direct methods to alleviate negative impacts on environment therefore the demand of efficient wind energy conversion system is increasing. Uneven distribution of wind impacts the performance of Wind Turbine (WT) system so constant and noise free power at output is required. The pitching angle varies according to the Wind Speed (WS), and the power output equation of the entire WT system depends upon WT pitch angle. Pitch control is widely used to optimize power above rated WS. This paper proposes an efficient adaptive pitch control controller to maintain the output power of a 5 MW WT in dynamic wind conditions. Compared to low level control loops (such as PI), this illustrates the effectiveness of the proposed controller. The model was tested in a 5 MW WT GH bladed system.